Anxiety Severity, Perceived Risk of COVID-19 and Individual Functioning in Emerging Adults Facing the Pandemic - Germani, Alessandro; Buratta, Livia; Delvecchio, Elisa; Gizzi, Giulia; Mazzeschi, Claudia (Frontiers in Psychology, 2020)
The COVID-19 pandemic is showing a strong impact on people in terms of uncertainty and instability it has caused in different areas of daily life. Uncertainty and instability are also emotions that characterize emerging adulthood (EA). They generate worries about the present and the future and are a source of anxiety that impacts negatively on personal and interpersonal functioning. Anxiety seems a central effect of the pandemic and recent studies have suggested that it is linked to COVID-19 risk perception. In the present study, a sample of 1045 Italian emerging adults was collected: (1) to assess anxiety severity and perceived risk related to COVID-19 and their association and (2) to compare general health and protective factors such as attitudes about security, relationships, self-esteem, and self-efficacy across anxiety severity and perceived risk categories. The findings of this study highlighted that anxiety severity categories were distributed homogeneously across the sample and that half of the participants referred to moderate-severe anxiety. A series of analysis of variances and post hoc comparisons showed that general health and all protective factors decreased according to anxiety severity. They were higher in participants with high perceived risk, with the exception of self-efficacy. Given the challenging features of the pandemic and EA, it is crucial to monitor anxiety severity in order to prevent last longing effects on mental and physical health, as well as keeping emerging adults informed about the risks related to the pandemic. Intervention and supportive programs based on improving self-esteem and self-efficacy, as well as confidence in relationships, should be offered to emerging adults over the long term, beyond the current outbreak.